Gastroscope Application in Difficult Colonoscopy: An Effective Alternative for Patients with Gynecologic Oncology - Linna Luo; Wei Qiao; Xinxin Huang; Yin Li; Jianjun Li; Wencheng Tan; Longjun He (IMR Press, 2024)
Background: Whole-colon examination is crucial for patients with gynecologic oncology, which somehow presents challenges in some cases. This study is aiming to investigate the effectiveness of gastroscope applied in difficult colonoscopy among such patients. Methods: Patients with gynecologic oncology who underwent colon examination were assessed and categorized into two groups, gastroscope replacement group (GR-group) and normal colonoscopy group (NC-group). Gastroscope was applied in the challenging cases within GR-group following unsuccessful attempts for colonoscopy. The assessment encompassed various features, including body mass index (BMI), nutritional indicators, previous therapeutic history, and the number and size of gynecologic oncology. A multivariate analysis was performed to screen out high-risk features for difficult colonoscopy, and a model was developed to evaluate the appropriateness of gastroscope application in such instances. Decision curve analysis was conducted to evaluate the clinical usefulness of the model. Results: We retrospectively collected the clinical characteristics of 171 patients with gynecologic oncology who underwent colon examinations, with 19 cases and 20 cases of difficult colonoscopy in GR-group and NC-group, respectively. The success rate of passing through the narrow site was 63% for the GR-group and 60% for the NC-group (p = 1.000). High risk factors of difficult colonoscopy included a BMI ≤18 kg/m2 (p = 0.03) and post-treatment status (p < 0.01). The evaluation model, constructed from clinical features, demonstrated excellent discrimination with an area under curve (AUC) of 0.86, offering significant net benefits to the validation group. Conclusions: A low BMI and post-treatment status emerged as independent risk factors for difficult colonoscopy in patients with gynecologic oncology. In such cases, gastroscope proved to be an effective and reliable alternative for the colon examination. The current findings are promising to be put into clinical use after verification by large-scale prospective studies.